2023
DOI: 10.3390/cancers15174299
|View full text |Cite
|
Sign up to set email alerts
|

TNFR1 and TNFR2, Which Link NF-κB Activation, Drive Lung Cancer Progression, Cell Dedifferentiation, and Metastasis

Gongping Shi,
Yinling Hu

Abstract: TNFR1 and TNFR2, encoded by TNFRSF1A and TNFRSF1B, respectively, are the most well-characterized members among the TNFR superfamily. TNFR1 is expressed in most cell types, while TNFR2 has been reported to be preferentially expressed in leukocytes. Lung cancer remains the leading cause of cancer mortality worldwide but TNFRs’ activities in lung cancer development have not been fully evaluated. Recently, overexpressed TNFR1 was reported in a large proportion of human lung squamous cell carcinomas. Increased TNFR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…TNFRSF1A and TNFRSF1B are the most well-characterized members of the TNFR superfamily ( 47 ). TNFRSF1B is preferentially expressed in leukocytes, while TNFRSF1A is reported to be expressed in most cell types ( 48 , 49 ). Nevertheless, the present study indicated that the interactions of TNF-TNFRSF1A exhibited greater specificity than those of TNF-TNFRSF1B within renal cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…TNFRSF1A and TNFRSF1B are the most well-characterized members of the TNFR superfamily ( 47 ). TNFRSF1B is preferentially expressed in leukocytes, while TNFRSF1A is reported to be expressed in most cell types ( 48 , 49 ). Nevertheless, the present study indicated that the interactions of TNF-TNFRSF1A exhibited greater specificity than those of TNF-TNFRSF1B within renal cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Overexpression of TNFR1 is also found in lung adenocarcinoma, but TNFR2 has a different role. Stimulation of TNFR2 by TNF- produced by macrophages converts CD4 T lymphocytes into Treg cells that play a role in the progression of lung adenocarcinoma [16].…”
Section: International Journal Of Scientific Advances Issn: 2708-7972mentioning
confidence: 99%
“…TNF receptors are well characterized and intensively studied [ 3 ]. The most well-known specific TNF receptor is TNFR1 [ 4 ]. TNFR1 is present in many tissues on various cells, including tumor cells [ 5 ].…”
mentioning
confidence: 99%